Child and adolescent exposure to alcohol advertising in Australia's major televised sports. (14th September 2015) - Carr, Sherilene; O'Brien, Kerry S.; Ferris, Jason; Room, Robin; Livingston, Michael; Vandenberg, Brian; Donovan, Robert J.; Lynott, Dermot
Abstract: Introduction and Aims: Exposure to alcohol advertising is associated with greater alcohol consumption in children and adolescents, and alcohol advertising is common in Australian sport. We examine child, adolescent and young adult exposure to alcohol advertising during three televised sports in Australia: Australian Football League (AFL), cricket and the National Rugby League (NRL). Methods: Alcohol advertising and audience viewing data were purchased for all AFL, cricket and NRL TV programs in Australia for 2012. We estimated children and adolescents (0–17 years) and young adults (18–29 years) exposure to alcohol advertising during AFL, cricket and NRL programs in the daytime (06:00–20:29 h), and night‐time (20:30–23:59 h). Results: There were 3544 alcohol advertisements in AFL (1942), cricket (941) and NRL programs (661), representing 60% of all alcohol advertising in sport TV, and 15% of all alcohol advertisements on Australian TV. These programs had a cumulative audience of 26.9 million children and adolescents, and 32 million young adults. Children and adolescents received 51 million exposures to alcohol advertising, with 47% of this exposure occurring during the daytime. Children and adolescents exposure to alcohol advertising was similar to young adults and peaked after 8.30pm. Discussion and Conclusions: Child and adolescent and young adult's exposure to alcohol advertising is high when viewing sport TV in Australia in the daytime and night‐time. Current alcohol advertising regulations are not protecting children and adolescents from exposure, particularly in prominent televised sports. The regulations should be changed to reduce children and adolescent excessive exposure to alcohol advertising when watching sport. [Carr S, O'Brien KS, Ferris J, Room R, Livingston M, Vandenberg B, Donovan RJ, Lynott D. Child and adolescent exposure to alcohol advertising in Australia's major televised sports. Drug Alcohol Rev 2016;35:406–411]